How money works the facts visually explained - Harzog, Beverly Blair (New York DK, 2017)
Money facilitates the billions of transactions that take place every day across the globe. Using ?need to know? boxes, step-by-step diagrams, and other eye-catching visuals, How Money Works shows you how this is possible. It explains economic theories, how governments raise and control money, what goes on in the stock exchange, how analysts predict where shares are heading, and many other issues. It busts jargon, explaining terms such as quantitative easing, cash flow, bonds, superannuation, and the open market.
Includes index.
Keywords: Money